Políticas de financiamento estudantil: Análise de impacto do Fies no tempo de conclus\~ao do ensino superior - Kalinca Lea Becker; Mário Jorge Cardoso de Mendonça (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– This study evaluated the impact of Fies on the total time and delay in the completion of higher education of students enrolled in presential courses of private institutions, based on information of INEP from 2007 to 2017. Estimates of the Average Treatment Effect on Treated indicated that participation in Fies increased both the results analyzed, total time and delay. In the first phase of the policy, from 2000 to 2009, the increase in completion time for students who received Fies was 8.5 months. In the second phase, from 2010 to 2014, which is characterized by the loosening of the rules for the granting and payment of the loan, the increase was 2.4 years. In the case of the delay in completing the course, the result was significant only in the 2nd phase, indicating an increase of 1.8 years for the students who received the Fies. In this view, it is necessary to introduce incentive mechanisms in the student credit granting policies in order that the student completes the course in regular time.
Keywords: D22; H52; I21; 330; credit for education; Fies; completion time; propensity score matching; entropy